(3eNJUQ ebGdI LGdjfhS aj GdMK Ydi JYde GdYdhe hGdUfGYGJ Z e HgG fXGe GdJYbjHIs - (3CHhRcQjG Hf YOi GdajSha GdfUQGfi GdjYbhHis
(3ChdgG (B:s
(3bd CeG GdCeQ ai GdMjhGf GdPi jSei ZjQ fGWb dGfWb dg GdHJI s
(3BNQgG (B:s
(3dG Cf jYOhG cGdaQS hGdBQGfH s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdKGefIs
(3HgG fXGe GdJYbjHIs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3CNdGb JjehQ (B290) s
Keywords: (3GdadSaI hGdefWbs